(untitled) (Fiep Bulletin - online, 2011)
Self-knowledge and self-concept are essential to the formation of an individual, and it is a function of the school to contribute to the construction of a national autonomous citizen in social actions and practices, as well as producers and carriers of ideas, and leaders of the pedagogical action, inventing themselves in the relationships established and constituting themselves as subjects in re-appropriation of knowledge (Foucault, 1999, apud Oliveira, 2003). Practitioners of Physical Education, in view of the new ways in which society progresses and conceptualizes the physicality, need to recognize the new paradigm with a view to provide critical position in relation to new standards. Addressing such questions is, in and out of school, taking positions that call into question charges that determine rigid standards of beauty which cause more and more dissatisfaction with their bodies.